2020
DOI: 10.1111/add.14889
|View full text |Cite
|
Sign up to set email alerts
|

Frequent intoxication and alcohol tolerance in adolescence: associations with psychiatric disorders in young adulthood

Abstract: AimsTo assess the associations of intoxication frequency and number of drinks needed to become intoxicated in mid-adolescence with onset of psychiatric disorders in early adulthood. Design, Setting and Participants Prospective cohort study in Northern Finland, with people from the Northern Finland Birth Cohort 1986 who self-reported adolescent alcohol use: 6548 subjects (69.4% of the original sample). Data on alcohol use were collected using questionnaires at ages 15-16 years. Measurements Outcomes were any no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Note that, despite the increased persistence of tolerance at younger ages, this was not accompanied by better prediction of AD course or alcohol use among younger adults (i.e., the absence of interaction with age indicates similar prediction among younger and older participants). In addition to the main effect of tolerance predicting AD new onset, this was one of the three criteria that were consistently associated with alcohol use measures at Wave 1, which is consistent with findings indicating a stronger association with alcohol consumption than with externalizing psychopathology (McDowell et al, 2019; see also Sarala et al, 2020). In sum, our results did not reveal the overendorsement of tolerance among younger individuals suggested by some studies (Harford et al, 2009;Pabst et al, 2012;Saha et al, 2006), but were consistent with at least one study showing that young adults do not misinterpret questions about tolerance (Slade et al, 2013).…”
Section: Tolerancesupporting
confidence: 84%
“…Note that, despite the increased persistence of tolerance at younger ages, this was not accompanied by better prediction of AD course or alcohol use among younger adults (i.e., the absence of interaction with age indicates similar prediction among younger and older participants). In addition to the main effect of tolerance predicting AD new onset, this was one of the three criteria that were consistently associated with alcohol use measures at Wave 1, which is consistent with findings indicating a stronger association with alcohol consumption than with externalizing psychopathology (McDowell et al, 2019; see also Sarala et al, 2020). In sum, our results did not reveal the overendorsement of tolerance among younger individuals suggested by some studies (Harford et al, 2009;Pabst et al, 2012;Saha et al, 2006), but were consistent with at least one study showing that young adults do not misinterpret questions about tolerance (Slade et al, 2013).…”
Section: Tolerancesupporting
confidence: 84%
“…Adolescent illicit substance use has been reported to elevate the risk of anxiety and mood disorder (Fergusson et al, 2002; Sareen et al, 2006; Wang et al, 2018). Moreover, adolescent smoking and frequent intoxication has been associated with SUD in young adulthood (Riala et al, 2004; Sarala et al, 2020). Adolescents with substance use may be predisposed to later psychiatric disorders through the disruption of critical processes of brain development (Lubman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies examining the mental health outcomes associated with peer aggression, there has been limited attention to the potential confounding role of adolescent substance use. To the best of our knowledge, there are only two previous studies that adequately adjusted for adolescent onset substance use (Copeland et al, 2013; Moore et al, 2014), despite it being identified as being a potential risk factor for mental disorders in young adults (Moylan et al, 2013; Mustonen et al, 2018; Sarala et al, 2020). Moore et al (2014) observed an association between being a perpetrator of peer aggression at 14 years and harmful alcohol use at 17 years after adjusting for baseline substance use problems (Moore et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has suggested that this may be the result of confusing the sequelae of acute intoxication with alcohol withdrawal and rapid initial tolerance with the chronic tolerance reported in the context of AUD. A recent study found that high self-reported alcohol tolerance in adolescence is associated with subsequent substance use disorder (SUD) in young adulthood [14]. However, very little is known about the link between alcohol tolerance in adolescence and subsequent mortality.…”
Section: Implications and Contributionmentioning
confidence: 99%